QT dispersion in type 2 diabetic patients with altered diurnal blood pressure rhythm - FAK, ALİ SERDAR; YAVUZ, DİLEK (WILEY, 2005)
Background: QT dispersion (QTd) is a good prognostic marker in type 2 diabetic patients without previous cardiovascular disease. Diabetic patients with an attenuated decline in nocturnal blood pressure (non-dippers) have been shown to have increased risk of diabetic complications, vascular events and mortality. Aim: The aim of this study was to evaluate the relationship between diurnal blood pressure rhythm, QTd and microvascular complications in type 2 diabetic patients. Methods: Cardiovascular autonomic function tests, 24-h ambulatory blood pressure monitoring and urinary albumin excretion measurements were performed in healthy controls (n = 25), normoalbuminuric (n = 34) and microalbuminuric (n = 23) type 2 diabetic patients. QTd was assessed manually from 12-lead surface electrocardiograms. Results: Compared with the controls, both normoalbuminuric and microalbuminuric diabetic patients had increased QTd (59.11 +/- 15.86; 60.27 +/- 17.95 vs. 40.48 +/- 10.92, p < 0.001 and p < 0.001, respectively). Similarly, diabetic patients had increased QTd regardless of the presence of autonomic neuropathy. On the other hand, non-dipper diabetic patients had increased QTd compared with the controls and dipper diabetic patients (69.73 +/- 14.50 vs. 40.48 +/- 10.92; 47.84 +/- 9.62 ms, p < 0.001). There was a negative correlation between QTd and diurnal diastolic blood pressure change (r = -0.48, p < 0.0005). Conclusion: Patients with type 2 diabetes mellitus were found to have increased QT dispersion irrespective of the presence of diabetic autonomic neuropathy. However, QT dispersion in dipper diabetic patients was similar to the controls. This finding might point out that attenuated decline of nocturnal blood pressure could be a more sensitive marker for autonomic neuropathy.
Keywords: ambulatory blood pressure; diabetes mellitus; microvascular complications; QT dispersion; LEFT-VENTRICULAR HYPERTROPHY; NIDDM PATIENTS; CARDIAC DEATH; FOLLOW-UP; MORTALITY; RISK; IDENTIFICATION; HYPERTENSION; NEPHROPATHY; ASSOCIATION